Big Data and Thriving Cities : Innovations in Analytics to Build Sustainable, Resilient, Equitable and Livable Urban Spaces - Monroe, Trevor (World Bank, Washington, DC, 2017)
The recent global diffusion of new technologies, combined with the use of big data analytics, can help policymakers promote the effective development of future cities that provide living and work environments in which citizens can thrive. In particular, innovative applications of geospatial and sensing technologies and the penetration of mobile phone technology are providing unprecedented data collection This data can be analyzed for many purposes, including tracking population and mobility, private sector investment, and transparency in federal and local government. To help development practitioners within and beyond the World Bank take advantage of these trends, this brief profiles a sample of big data applications to support improved urban development in low- and middle-income countries. It also cites potential opportunities for big data analytics to help developing nations achieve sustainable urban growth, while reducing the economic differential with high-income countries.